Valproic acid promotes a decrease in mycobacterial survival by enhancing nitric oxide production in macrophages stimulated with IFN-γ. (January 2019) - Nieto-Patlán, Erik; Serafín-López, Jeanet; Wong-Baeza, Isabel; Pérez-Tapia, Sonia M.; Cobos-Marín, Laura; Estrada-Parra, Sergio; Estrada-García, Iris; Chávez-Blanco, Alma D.; Chacón-Salinas, Rommel
Abstract: Tuberculosis is one of the leading causes of mortality worldwide, it is caused by Mycobacterium tuberculosis (Mtb), a bacteria that employs several strategies to evade the host immune response. For instance, Mtb interferes with the overexpression of class II transactivator (CIITA) in macrophages exposed to IFN-γ by inhibiting histone acetylation at its promoter, which can be reverted by the histone deacetylase inhibitor (HDACi) sodium butyrate. In this work, we evaluated whether a different HDACi, valproic acid (VPA), could revert the inhibition of gene expression induced by Mtb. J774 macrophages treated with VPA and IFN-γ unexpectedly induced a higher expression of the inducible nitric oxide synthase and a higher production of nitric oxide when exposed to the 19 kDa lipoprotein of Mtb or the whole bacteria. However, VPA was unable to revert the inhibition of CIITA expression induced by the 19 kDa lipoprotein of Mtb. Finally, macrophages infected with Mtb and treated with VPA and IFN-γ showed a significant reduction in intracellular bacteria. Our findings suggest a new therapeutic potential of VPA for the treatment of tuberculosis.